Corporate governance and regulatory impact on mergers and acquisitions: research and analysis on activity worldwide since 1990 - Gregoriou, Greg N. 1956-; Renneboog, Luc (Quantitative finance series.)
Corporate Governance and regulatory presssures have been much in the news lately. How they affect the bottom line of corporations has been difficult to quantify, and research is just beginning to be published that addresses this crucial question. This book is the first collection of new research about the impact of takeover regulation and corporate governance on M & A financial results. It will be essential reading to any M & A specialist, an investment banker, a hedge fund manager, a private equity director, or a venture capitalist. Also a must read for financial analysts who follow M & A targets. The book presents research from around the world so it provides a global perspective on this important topic. *The first and only book of research on takeover regulation and corporate governance affecting M & A results *Stands out from all the "How to" books on M & A and M & A disaster books because it provides solid high-quality research on what works and how different decisions affect company and shareholder value *Research provides a guideline for decisionmakers in investment banks, private equity companies, and for financial analysts.